Aspergillus genus as a source of new catalysts for sulfide oxidation - Mascotti, María Laura (2012)
This work extends the present knowledge about the ability of filamentous fungi to selectively transform sulfur-containing compounds. Here, it has been demonstrated that several species of the Aspergillus genus are able to perform chemo- and stereoselective oxidation of organic sulfides. Two substrates were chosen as models, the aliphatic cyclohexyl(methyl)sulfide and the alkyl aryl sulfide, thioanisole. All the tested strains showed the ability to oxidize cyclohexyl(methyl)sulfide, whereas most of them oxidized thioanisole. In all cases R-stereoselectivity was observed and full chemoselectivity was verified since no sulfone was detected. Several biotransformation parameters such as the employment of growing or resting cell, different head-space volumes, age of the cultures, bio-reaction times and biocatalyst/substrate ratios resulted crucial in the optimization of the processes. Thus, when using isopropyl alcohol as co-solvent in growing cell systems, chemo- and stereoselectivity could be modulated. Among the studied strains, Aspergillus japonicus ICFC 744/11 was found to be a promising whole cell biocatalyst to prepare enantioenriched sulfoxides since after optimization, either conversion and optical purity of (R)-cyclohexyl(methyl)sulfoxide were excellent (c: 100%, ee > 99%). © 2012 Elsevier B.V.